Genetic diversity within and among two Argentinean and one Mexican species of Acacia (Fabaceae) - Pometti, Carolina Luciana (2015)
Acacia is a pantropical genus comprising>1450 species. Following Vassal's treatment Acacia is considered as a single genus with three subgenera (Acacia, Aculeiferum and Phyllodineae). Acacia caven, A.curvifructa and A.farnesiana belong to subgenus Acacia and the relationship between them is controversial. The aim of this study was to elucidate the relationship between the three species using amplified fragment length polymorphism, analysing 15 populations of these species, and to compare the results obtained with those from a morphological analysis. Genetic diversity indices (percentage of polymorphic loci, genetic diversity) showed that genetic variation in A.caven is higher than that in A.curvifructa and A.farnesiana. Of the total genetic diversity in A.caven and A.farnesiana, most is found within populations (∼70%). Analysis with STRUCTURE showed that the optimal number of clusters (K) was ten, and in all cases where populations were grouped they were geographically close and/or belong to the same variety. The morphological canonical discriminant analysis did not result in a separation between all individuals, indicating that they do not harbour consistent morphological discontinuities. Altogether, the results of our molecular analyses showed the existence of significant differences between A.caven, A.curvifructa and A.farnesiana, which argues for recognizing them as different species.